2009
DOI: 10.1089/scd.2008.0213
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Differentiation in an Experimental Cartilage Defect: Restriction of Hypertrophy to Bone-Close Neocartilage

Abstract: Mesenchymal stem cells (MSCs) are promising for the treatment of articular cartilage defects; however, common protocols for in vitro chondrogenesis induce typical features of hypertrophic chondrocytes reminiscent of endochondral bone formation. Aim of the study was to compare chondrogenic differentiation of MSCs in vitro and in vivo in experimental full-thickness cartilage defects, asking whether MSCs can differentiate into collagen type X-negative chondrocytes in an orthotopic environment. Cartilage defects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 31 publications
3
89
0
1
Order By: Relevance
“…The adverse events of matrix calcification and hypertrophic changes were also much delayed and less significant in the ECM group. The defect area of the cartilage might not be the same as subcutaneous environment but is still under harsh conditions that are not favorable for chondrogenic differentiation and cartilage tissue formation of stem cells [36,37]. Therefore, we speculate that our ECM scaffold could also be a promising scaffold that can both support well chondrogenic differentiation of MSCs and reduce degenerative changes of engineered tissue in cartilage defect.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse events of matrix calcification and hypertrophic changes were also much delayed and less significant in the ECM group. The defect area of the cartilage might not be the same as subcutaneous environment but is still under harsh conditions that are not favorable for chondrogenic differentiation and cartilage tissue formation of stem cells [36,37]. Therefore, we speculate that our ECM scaffold could also be a promising scaffold that can both support well chondrogenic differentiation of MSCs and reduce degenerative changes of engineered tissue in cartilage defect.…”
Section: Discussionmentioning
confidence: 99%
“…modulus of engineered cartilage is known to be strongly correlated to the sGAG content (Kelly et al, 2007;Vinardell et al, 2011), the dynamic modulus also strongly depends on the functionality of the collagen network, as it plays a key role in enabling the tissue to generate fluid load support (Ateshian, 2009). Within full thickness cartilage defects, it has been demonstrated that hypertrophy of implanted MSCs is restricted to a region of the regenerating tissue close to the bone, suggesting that biomechanical stimuli play a key role in determining the stability of the chondrogenic phenotype (Steck et al, 2009). The results of this study support this hypothesis, with the application of HP found to dramatically reduce the mineralisation of BMSC constructs cultured in a chondro-inductive medium.…”
Section: Discussionmentioning
confidence: 99%
“…Within the orthotopic environment of a full thickness cartilage defect, it has been demonstrated that hypertrophy of implanted multipotent stromal cells (MSCs) is restricted to a region of the regenerating tissue close to the bone, demonstrating that in vivo signalling molecules and biomechanical stimuli play a key role in regulating the chondrogenic phenotypic (Steck et al, 2009). Identifying how such in vivo specific environmental cues regulate the terminal phenotype of MSCs may play a key role in realising their full therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it is not yet possible to steer the differentiation of MSCs into the formation of permanent hyaline cartilage. Instead, the present protocols for chondrogenically differentiating MSCs result in the production of neocartilage that is characterized by hypertrophic differentiation (6)(7)(8)(9). Consequently, the newly formed cartilage undergoes endochondral ossification upon implantation (8,(10)(11)(12).…”
mentioning
confidence: 99%
“…Instead, the present protocols for chondrogenically differentiating MSCs result in the production of neocartilage that is characterized by hypertrophic differentiation (6)(7)(8)(9). Consequently, the newly formed cartilage undergoes endochondral ossification upon implantation (8,(10)(11)(12). In fact, it has been reported that, currently, the most efficient way to engineer new bone from multipotent progenitor cells is via implantation of in vitro-generated neocartilage (6).…”
mentioning
confidence: 99%